Gdańsk : Stary Ratusz / Fot. J. Uklejewski. - Uklejewski, Janusz (1925-2011) (Spółdzielczy Instytut Wydawniczy "KRAJ", 1947)
Przedstawia ruiny ulicy Korzennej i Ratusza Starego Miasta, około 1947 roku.